RESPONE OF FORAGES BY ADMINISTRATION OF FERMENTED GOAT URINE - diana, nevy (Universitas Djuanda Bogor, 2019)
Urine goat fermentented can be used as organic fertilizers element hara on the ground For the agricultural crops and forage. Theof this study todetermine dosage of fermented goat urine onnumber of tillers, plant heightproduction of fresh dry matter,content of Phosphor and potassium on different forages (Pennisetum purpureum schumach), (Setaria sphacelata)and (Brachiaria brizantha). Experimental design usedfactorial with two factors, the first factor wasdose of fermented goat urine (liters /ha) composed of P0 = 0/ha,P1 = 10/ha, P2 = 15/haand P3 = 20/ha and the second factor was forages composed of R1 Pennisetum purpureum schumach, R2 Setaria sphacelataand R3 Brachiaria brizanta. The results showed that dosage of fermented goat urine and species of forage and interaction had significant effect (P<0.05) on number of tillers, plant height, fresh and dry weight production, phosphorus and potassium of plant.Increasing dosage, dosage fermented goat urine.Increase plantheight, fresh weight, dry weight production while, growth of Pennisetum purpureum schumach was higher than Brachiaria brizantha and Setaria sphacelata. The optimum dosage fermented goat urine on Pennisetum purpureum schumach was 20 liters/ha while on Brachiaria brizantha and Setaria sphacelata was 15 liters/ha. It is concluded that usage increase growth of forages and the best combination show on Pennisetum purpureum schumach with dosage at 20 liters /ha.Keywords: Forages, Urine goat fermented, productivity.